(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. In the current conditions of global transformation, the role and importance of regions is growing every year, because the rise of the differentiation of social and economic development is an extraordinary problem, which is extremely negative in the formation of a market economy. Today, the regions are not only becoming active stakeholders of international economic relations, but also are actively involved in the formation of relevant regional economic area, which become the background for the development of the country as a whole. That is why the analysis of terminological bases of social and economic development of the region is a topical issue, the research of which revealed that current economic science contains a huge number of alternative theories, models of growth and development of regions. It is worth noting the basic theories of regional development such as a theory of cumulative development, neoclassical theories, theories of regional growth and modern ones. Theories of regional development are formed on the basis of changes in interregional levels of development through the use of the mechanism of "natural market", according to which the factors of production are moved to those regions where they are paid more. Scientists focused on social, geographical, political indicators of development and logistics (transport) costs. According to the theory of regional growth of J. Borts and J. Stein, the changes taking place in the social and economic life are caused by the rapid development of factors of manufacturing. In the second half of XX century R. Solow, J. Mead, A. Lewis found out that positive growth was directly connected with the labor productivity, which depends on scientific and technological progress and effective management. R. Solow, emphasized that the main task of the theory is to equalize the level of development of highly developed and backward regions by increasing the rate of economic growth where these indicators are most critical [5]. The purpose of the article. It should be noted that in most works of foreign scholars there is no difference between "local" and "regional" development. Researchers usually emphasize that the consideration of "regional" or "local" development should be carried out on an interdisciplinary basis, considering all factors: geographical, economic, urban. The historical interpretation of economic development was narrowed only to the economic space: the basis of this development is an increase in income and employment. In the early 80’s of the last century, the nature, quality and sustainability of regional development become the focus in their social, cultural, political, environmental dimensions. Interregional inequalities in welth and living standards call into question traditional economic indicators, as to their adequate reflection of the nature and content of regional development. Thus, economic systems should be human-oriented aimed at development and increasing rates of economic growth. The purpose of the regional economy is to identify and develop the strengths of each region and reduce the negative impact of external factors, so as to create decent living conditions, ensuring jobs, implementing scientifically-based programs of socio-economic development of a particular region (taking into account geographical, political, social characteristics) Results. Thus, the study of the evolution of scientific thought on regional development makes it possible to identify basic theories and concepts and characterize their evolutionary conditionality. It was found that the early theory of stimulating regional development took into account only economic factors, but the process of evolution and cyclicality makes it impossible to study regional competitiveness beyond the social, geographical conditions of a particular region. Most theories and concepts about regional development appeared in the 70s and 90s of the last century. All of them are based on the fact that the achievement of high socio-economic indicators mainly depends on the quality of management, not just on the resource potential. Differing in fundamental approaches, theories and concepts offer different mechanisms of influence on the state of territories, taking into account the location of economic objects, their interaction with the external environment, interaction and partnership at the local level, human potential and others. To some extent, each theory reflects the essence of the current processes of any region at some stage of its development. The vector of scientific research in this area is shifting from the macro level to the macro level. Therefore, our next research will focus on the study of decentralization processes at different regional levels.